2005
DOI: 10.1051/animres:2005023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fatty acid composition and softness score of adipose tissue in intensively reared lambs fed with concentrate based on cereals or on beet pulp

Abstract: -The aim of the study was to investigate the effect of substituting cereals by sugar beet pulp in the feed on the fatty acid (FA) composition of subcutaneous adipose tissue in indoor lambs. Forty-nine male lambs of the Lacaune dairy breed were fed from 23.6 (± 4.1) to 41.0 (± 1.9) kg live weight with hay and a pelleted concentrate containing either 80% of barley and wheat (group C) or 70% sugar beet pulp (group P). The FA composition of caudal adipose tissue sampled at slaughter was determined. The subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…There was also an absence of effect of linseed on colour parameters; this result is in agreement with those of some studies (Dumont et al 1997;Normand et al 2005) and in disagreement with some others (Ponnampalam et al 2002;Demirel et al 2004). The latter noted that meat with more unsaturated FAs is more susceptible to oxidation, resulting in a colour modification.…”
Section: Growth Performance and Meat Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…There was also an absence of effect of linseed on colour parameters; this result is in agreement with those of some studies (Dumont et al 1997;Normand et al 2005) and in disagreement with some others (Ponnampalam et al 2002;Demirel et al 2004). The latter noted that meat with more unsaturated FAs is more susceptible to oxidation, resulting in a colour modification.…”
Section: Growth Performance and Meat Characteristicssupporting
confidence: 88%
“…In fact, all concentrates have similar energetic and nitrogenous values. The lack of effect of linseed supplementation on lamb's growth was shown in other studies (Demirel et al 2004;Normand et al 2005;Bas et al 2007). …”
Section: Growth Performance and Meat Characteristicsmentioning
confidence: 64%
“…As ALA proportion had a loading score orthogonal to the PC1 axis, it confirmed that, even when lambs were fed diets rich in ALA, softer and more colored AT was directly related to high proportions of Odd-FA and OBCFA and to lower proportions of even-saturated FA. This has already been observed in lambs fed high concentrate diets (Bas, Giral, & Rouzeau, 1998;Miller, Kunsman, & Field, 1980;Normand et al, 2005;Orskov, Duncan, & Carnie, 1975).…”
Section: Effect Of Ewe Linseed Supplementation and Lamb Linseed Supplsupporting
confidence: 58%
“…All GC procedures are described in Berthelot et al (2010). Methyl branched chain FA were identified from length equivalent chains (LEC, Miwa, Mikolajzack, Earle, & Wolff, 1960) by interpolation between two consecutive saturated FA and compared to methyl ester standard mixtures (Sigma, St. Louis, MO) injected the same way for iso and anteiso-FA and FA previously identified by electron impact mass spectrometry for other methylbranched chain FA (OBCFA, Berthelot, Bas, Schmidely, & Duvaux-Ponter, 2001;Berthelot, Normand, Bas, & Kristensen, 2001;Normand, Bas, Berthelot, & Sauvant, 2005). Proportions of C18:1 isomers separated on the CP-SIL column were determined in relation with the proportion of the C18:0 obtained on the DB-wax column.…”
Section: Chemical Analysismentioning
confidence: 99%